Validation of the Polish PPQ-II: sociodemographic and clinical correlates of perinatal PTSD - Szablewska, Anna Weronika; Wójcicka, Lucyna; Prajzner, Arkadiusz; Zdun-Ryżewska, Agata; Burdecka, Julia; Klasa-Mazurkiewicz, Dagmara (Frontiers in Psychology, 2025)
BackgroundPerinatal PTSD (CB-PTSD) is a significant psychological condition that may affect mothers after childbirth, with long-term consequences for mental health. Despite growing global interest, limited research has addressed its prevalence and risk factors in Poland. This study aimed to validate the Polish version of the Perinatal PTSD Questionnaire (PPQ-II) and to explore sociodemographic and clinical correlates of CB-PTSD among Polish mothers.MethodsA cross-sectional study was conducted in December 2024 with a sample size 273 Polish mothers using the Computer-Assisted Web Interview (CAWI) method. The PPQ-II was adapted through translation, back-translation, and expert review. Psychometric evaluation included internal consistency, construct validity, and convergent validity with the PTSD-8 and DASS-21. Exploratory factor analysis (EFA) assessed the factor structure. Data analysis employed IBM SPSS 29.0 and Jamovi 2.4, with non-parametric tests examining associations with sociodemographic and clinical variables.ResultsEFA revealed two main domains: Avoidance/Intrusion and Arousal explaining 62% of total variance. The PPQ-II showed good internal consistency (Cronbach’s α = 0.90) and convergent validity. Results of Polish version of the PPQ-II were observed to be positively correlated with PTSD-8 (r = 0.43–0.85) and DASS-21 (r = 0.54–0.78). Significant differences in PPQ-II scores were observed across delivery mode, birth complications, and neonatal ICU admission. Higher CB-PTSD symptoms were reported by women undergoing cesarean sections, those whose infants required intensive care, and mothers of children with congenital defects. Lower socioeconomic status was also associated with higher scores.ConclusionThe Polish adaptation of the PPQ-II demonstrates strong reliability and validity for assessing perinatal PTSD. Maternal sociodemographic and clinical factors—particularly delivery method, neonatal complications, and socioeconomic conditions—substantially influence CB-PTSD severity. These findings emphasize the need for psychosocial assessment in perinatal care and targeted support for high-risk groups to mitigate adverse psychological outcomes.